Hepatotoxicity Due to Azole Antimycotic Agents in a HLA B*35:02-Positive Patient - Tim Bühler; Michael Medinger; Jamal Bouitbir; Stephan Krähenbühl; Anne Leuppi-Taegtmeyer (Frontiers Media S.A., 2019)
We will present a 42-year-old woman with acute myeloid leukemia and pulmonary aspergillosis. She was treated with several antifungal agents, including three triazoles. Voriconazole, posaconazole, and isavuconazole all led to hepatocellular liver injury. Voriconazole administration led to a peak alanine aminotransferase (ALT) value of 1,793 U/L (normal range, 9-59 U/L). After posaconazole and isavuconazole treatment, ALT rose over 500 U/L. The typical course of events, exclusion of differential diagnoses, and normalization of the liver function tests (LFTs) after stopping the triazoles were highly suspicious for a drug-induced liver injury (DILI). Interestingly, our patient carries a rare HLA B allele (HLA B*35:02), which occurs in less than 1% of the population and is known to be associated with minocycline-induced liver injury. Over the course of 4 months, the patient received two induction chemotherapies and afterward underwent a successful allogenic hematopoietic stem cell transplantation. Her liver function recovered rapidly and favorable clinical findings concerning the aspergillosis led to a de-escalation of the antifungal treatment to prophylactic dose fluconazole. Delayed hepatotoxicity suggested a dose dependency and a cumulative effect. The question of a common pathophysiology and a cross-toxicity was raised. At the present time, only a few case reports describe cross-toxicity or its absence after rechallenge with different azoles. The pathophysiology is not well understood. Ketoconazole was found to impair rat mitochondrial function in vitro. Further investigations showed cell membrane toxicity and ATP depletion in isolated human liver cancer cells. Our case report suggests a cross-toxicity, dose-dependency, and a possible genetic predisposition of triazole-induced liver injury.